Limb Ischemia Complications of Veno-Arterial Extracorporeal Membrane Oxygenation - Hu, Sixiong; Lu, Andong; Pan, Chenliang; Zhang, Bo; Wa, Yong ling; Qu, Wenjing; Bai, Ming (Frontiers in Medicine, 2022)
Background: This study aimed to summarize and analyze the risk factors, clinical features, prevention and treatment of limb ischemia complications in patients on veno-arterial extracorporeal membrane oxygenation (V-A ECMO). Methods: We retrospectively analyzed 179 adult patients who had undergone V-A ECMO support in the Cardiac Care Unit of the First Hospital of Lanzhou University between March 2019 and December 2021. The patients were divided into the limb ischemia group (LI group) and the non-limb ischemia group (nLI group) according to status of ipsilateral limb ischemia. The LI group was salvaged with distal perfusion cannula (DPC) according to each patient’s clinical condition. The baseline data of the two groups were compared, and risk factors for limb ischemia were screened using a multiple logistic regression analysis. Results: Overall, 19 patients (10.6%) had limb ischemia complications, of which 5 (2.8%) improved after drug treatment, 12 (8.4%) were salvaged with DPC, and two had undergone surgical intervention. There were significant differences in the extracorporeal membrane oxygenation-assisted cardiopulmonary resuscitation (ECPR), intra-aortic balloon pump (IABP), vasoactive-inotropic score (VISmax), left ventricular ejection fraction (LVEF), weaning from ECMO, and discharge rate between the two groups. ECPR, combined IABP, and VISmax in the LI group were significantly higher than those in the nLI group, whereas weaning from ECMO, discharge rate, and LVEF were significantly lower in the LI group compared to those in the nLI group. Furthermore, multiple logistic regression analysis showed that diabetes mellitus (odds ratio [OR]=4.338, 95% confidence interval [CI]:1.193-15.772, P=0.026) combined with IABP (OR=1.526, 95% CI:1.038-22.026, P=0.049) and VISmax (OR=1.054, 95% CI:1.024-1.085, P˂0.001) were independent risk factors for limb ischemia complications in patients undergoing V-A ECMO. Conclusion: Independent risk factors for predicting limb ischemia complications in patients who underwent V-A ECMO included diabetes combined with IABP and VISmax. Limb perfusion should be evaluated after the establishment of V-A ECMO, and salvage placement of DPC can be used as a measure for the prevention and treatment of limb ischemia complications.